2006
DOI: 10.1002/bp060226r
|View full text |Cite
|
Sign up to set email alerts
|

Diffusion of [3H]Dexamethasone in Rat Subcutaneous Slices after Injection Measured by Digital Autoradiography

Abstract: A relatively simple method for the determination of the diffusion coefficient of a substance that has been injected into tissue is described. We illustrate this method using [3]dexamethasone injected into the subcutaneous tissue of rats. Digital autoradiography was used to measure the distribution of the [3H] dexamethasone within the subcutaneous tissue at 2.5 and 20 min after injection. Measured concentration profiles of the injection were compared to a mathematical model of drug diffusion from an injection. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2007
2007
2015
2015

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 7 publications
0
5
0
Order By: Relevance
“…Moussy and coworkers have explored the effect of dexamethasone (DEX) on the foreign body response and found that DEX slowly released from microspheres had a beneficial effect on the foreign body response to subcutaneously‐implanted sutures in rats 24. In an attempt to understand the spatial effect of locally released steroids, they also found that the primary effect of DEX was confined to a very small area (several mm), as verified by direct in vivo measurement, mathematical modeling,6 and autoradiography in subcutaneous tissue slices 25. The Burgess laboratory has demonstrated the use of a PLGA microsphere‐based controlled release system to release DEX in concert with angiogenic growth factors 7, 26, 27.…”
Section: Discussionmentioning
confidence: 92%
“…Moussy and coworkers have explored the effect of dexamethasone (DEX) on the foreign body response and found that DEX slowly released from microspheres had a beneficial effect on the foreign body response to subcutaneously‐implanted sutures in rats 24. In an attempt to understand the spatial effect of locally released steroids, they also found that the primary effect of DEX was confined to a very small area (several mm), as verified by direct in vivo measurement, mathematical modeling,6 and autoradiography in subcutaneous tissue slices 25. The Burgess laboratory has demonstrated the use of a PLGA microsphere‐based controlled release system to release DEX in concert with angiogenic growth factors 7, 26, 27.…”
Section: Discussionmentioning
confidence: 92%
“…An intravaginal environment on the other hand, while providing defined and homeostatically controlled temperature and internal pressure at the matrix surface, putatively entails additional mass transport of sublimed matrix vapors away from the eroding surface via a series of diffusion and convection steps typically observed for implanted devices (36,37). Adult ewes were chosen for an animal model due to their average intravaginal surface area being very similar to the average value measured in women (23,38,39).…”
Section: Resultsmentioning
confidence: 99%
“…The diffusion coefficient was estimated from the known value for dexamethasone in the subcutaneous tissue. 14 Note that the molecular masses of dexamethasone and salubrinal are 392 Da and 480 Da, respectively.…”
Section: Methodsmentioning
confidence: 99%